Unplanned Hospital Readmission and Visit to the Emergency Room in the First Thirty Days after Head and Neck Surgery: A Prospective, Single-center Study - Chiesa-Estomba,Carlos Miguel (2022)
Abstract Introduction Head and neck surgery remains a complex field; the patients can suffer important functional or life-threating complications after treatment that need unplanned readmissions, increasing the cost related to the treatment. Objective To evaluate the incidence risk factors and causes associated with 30-day unplanned hospital readmission and visit to the emergency room (ER) after surgery for head and neck cancer. Methods Prospective, longitudinal, nonrandomized study. Results A total of 834 patients were included, 726 in the major surgery group and 108 in the minor surgery group. The 30-day readmission rate for all causes was of 7,9% for the patients treated by a major surgery and of 0% for the patients treated in the outpatient clinic for minor procedures, to a total readmission rate of 6,8%. The rate of visit to the emergency room for all causes in the first 30 days was of 14% for the patients treated by a major surgery and of 2,7% for the patients treated in the outpatient clinic. Conclusion Major surgery, the American Society of Anesthesiologists (ASA) status and type of wound are conditions related to unplanned readmission or visit to the ER in the first 30 day after discharge. The most commonly associated causes are infections or wound complications. An evidence-based risk stratification of the patients can be important to improve decision-making and resource utilization. An educational strategy can provide possible ways to improve the rate of readmission and reduce the amount of money expended by healthcare systems.